1962
DOI: 10.1128/jb.84.4.797-802.1962
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Degradation of Tetracyclines

Abstract: The degradation of tetracyclines by an ascomycete, Xylaria digitata, was demonstrated. Washedcell suspensions were capable of degrading tetracycline, 5-hydroxytetracycline, 7-chlortetracycline, 7-chlor-6-demethyltetracycline, 2-acetyl-2-decarboxamido-5-hydroxytetracycline, and 12a-deoxytetracycline. The influence of environmental conditions upon the degradation of tetracycline was investigated. A nonantibacterial, nonfluorescent product was located from the degradation of 14C 5-hydroxytetracycline. Evidence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1963
1963
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Under soil acidic condition, OTC was epimerized in swine manure and formed degradation products such as 4epi-OT and epi-N-desmethyl-OT [27,35]. Ingerslev et al [36] found that biodegradation of TCs was the main mechanism in sludge by Ascomycetes fungi [37] and Streptomyces species; however, sorption and transformation of TCs commonly occurred in soil [27,32]. Our study confirmed that the transformation and stability of TCs in sediment and soil are dependent on light, temperature, and physiochemical properties of the matrix [38].…”
Section: Antibiotic Concentrations the Concentrations Of Tcsmentioning
confidence: 99%
“…Under soil acidic condition, OTC was epimerized in swine manure and formed degradation products such as 4epi-OT and epi-N-desmethyl-OT [27,35]. Ingerslev et al [36] found that biodegradation of TCs was the main mechanism in sludge by Ascomycetes fungi [37] and Streptomyces species; however, sorption and transformation of TCs commonly occurred in soil [27,32]. Our study confirmed that the transformation and stability of TCs in sediment and soil are dependent on light, temperature, and physiochemical properties of the matrix [38].…”
Section: Antibiotic Concentrations the Concentrations Of Tcsmentioning
confidence: 99%
“…Very few studies have been devoted to this regard. Meyers and Smith (1962) investigated the application of Xylaria digitata, a fungi to degrade tetracycline antibiotics and found out that they were effective. Other investigations involving the use of microbial degradation are reported by Maki et al (2006).…”
Section: Degradation Of Otc In Microcosm and Control Experimentsmentioning
confidence: 99%